Assessing the Determinants of Customer Loyalty under the Framework of Digital Customer Journey and Customer Lifetime Value - Firza Destrian Muhamad; Lingga Yuliana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digitalization has changed how hotel customers interact with services, making the digital customer journey increasingly important. The purpose of this study is to examine the influence of the digital customer journey, customer lifetime value, and customer loyalty. Theoretical contributions include providing an empirical understanding of the relationship between the digital customer journey, customer lifetime value, and customer loyalty within the hotel industry context. Meanwhile, practical contributions are provided by designing a digital strategy focused on improving the customer experience at every stage of the digital journey. Quantitative methods were used in this study. Purposive sampling was the sampling technique, involving 212 respondents who were Artotel customers. The data source was primary data using an online questionnaire. The data analysis technique used was partial least squares, processed using the SmartPLS version 4.1.0.0 analysis tool. The results show that the digital customer journey positively and significantly influences both customer lifetime value and customer loyalty. Customer lifetime value has a positive and significant influence on customer loyalty. The managerial implications of this study are that companies need to optimize long-term relationships with customers through data-driven loyalty programs and personalized services relevant to customer preferences.